A Selective reliable communication to reduce broadcasting for cluster based VANET - et.al, R. Shiddharthy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Vehicular Ad hoc Network (VANET) is one of the subset of Mobile Ad hoc Network (MANET) and it is a self-organised system with a group of vehicles, which are capable of short-range communication using On Board Unit (OBU). This unit is comprised with the vehicles that are possible to communicate with the nearby vehicles. VANETs rely on heavy broadcast transmission due to sharing data (messages) between the nearby vehicles about the traffic, collision and so on. This redundant information spoils the nature of VANET that affects the inter-vehicular communication, rebroadcasting and information on collision. This message transmission increases largely as the number of vehicles increases. This problem is typically named as broadcast storm and it is relatively reduced through the proposed Selective Reliable Communication (SRC) Protocol. Through a reliable communication, packets are retransmitted to reduce a number of transmission in the network within the acceptable level of QoS. The proposed SRC protocol automatically detect the vehicle clusters as “Zone of Interest”. Generally, the proposed protocol forwards the packets to the cluster-heads and the cluster-head forwards the packets to the cluster-members. The proposed protocol outperforms than the existing protocols in terms of Throughput, Packet Delivery Ratio (PDR) and Average delay.